Return to Sandakan - Quint, Raymond; Leatherdale, Julian; Film Australia (Australia: Film Australia, 1995)
During World War II, Sandakan prisoner of war camp in British North Borneo held nearly 2,500 allied prisoner, By war's end only 6 still alive. This documentary recounts a tragic story of prisoners of war : the use of forced labour, the death marches through the Borneo jungle and the rescue of only six survivors
'A Film Australia National Interest Program production'
Executive producer, Chris Oliver
Editor, Doug Howard ; researcher, Julian Leatherdale ; cinematographer, Philip Bull ; composer, Jan Preston ; historical consultants, Yuki Tanaka, Don Wall
Narrator: Ivar Kants
Keywords: Prisoners of war -- Australia; Prisoners of war -- Malaysia -- Sandakan (Sabah); World War, 1939-1945 -- Prisoners and prisons, Japanese